Ankle and knee kinetics between strike patterns at common training speeds in competitive male runners - Kuhman, D.; Melcher, D.; Paquette, M. R. (European Journal of Sport Science, 2016)
The purpose of this study was to investigate the interaction of foot strike and common speeds on sagittal plane ankle and knee joint kinetics in competitive rear foot strike (RFS) runners when running with a RFS pattern and an imposed forefoot strike (FFS) pattern. Sixteen competitive habitual male RFS runners ran at two different speeds (i.e. 8 and 6 min mile-1) using their habitual RFS and an imposed FFS pattern. A repeated measures analysis of variance was used to assess a potential interaction between strike pattern and speed for selected ground reaction force (GRF) variables and, sagittal plane ankle and knee kinematic and kinetic variables. No foot strike and speed interaction was observed for any of the kinetic variables. Habitual RFS yielded a greater loading rate of the vertical GRF, peak ankle dorsiflexor moment, peak knee extensor moment, peak knee eccentric extensor power, peak dorsiflexion and sagittal plane knee range of motion compared to imposed FFS. Imposed FFS yielded greater maximum vertical GRF, peak ankle plantarflexor moment, peak ankle eccentric plantarflexor power and sagittal plane ankle ROM compared to habitual RFS. Consistent with previous literature, imposed FFS in habitual RFS reduces eccentric knee extensor and ankle dorsiflexor involvement but produce greater eccentric ankle plantarflexor action compared to RFS. These acute differences between strike patterns were independent of running speeds equivalent to typical easy and hard training runs in competitive male runners. Current findings along with previous literature suggest differences in lower extremity kinetics between habitual RFS and imposed FFS running are consistent among a variety of runner populations.